2022
DOI: 10.1261/rna.079083.121
|View full text |Cite
|
Sign up to set email alerts
|

The Pet127 protein is a mitochondrial 5′-to-3′ exoribonuclease from the PD-(D/E)XK superfamily involved in RNA maturation and intron degradation in yeasts

Abstract: Pet127 is a mitochondrial protein found in multiple eukaryotic lineages, but absent from several taxa, including plants and animals. Distant homology suggests that it belongs to the divergent PD-(D/E)XK superfamily which includes various nucleases and related proteins. Earlier yeast genetics experiments suggest that it plays a nonessential role in RNA degradation and 5’ end processing. Our phylogenetic analysis suggests that it is a primordial eukaryotic invention that was retained in diverse groups, and indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 100 publications
(210 reference statements)
1
16
0
Order By: Relevance
“…84 Impaired RNA degradation leads to the accumulation of unprocessed precursors, introns and splicing intermediates, antisense (mirror) RNAs, and transcripts from intergenic regions of the genome. 11,12,[84][85][86] The mitochondrial genome of C. albicans, which is more compact and has shorter intergenic regions compared with S. cerevisiae, was shown to be transcribed in its entirety (pervasive transcription) in mutants deficient in the function of the main RNA degradation complex (mtEXO). 11 A range of ribonucleases, in mitochondria mostly those exhibiting exoribonuclease activities, act as general degradation factors involved in RNA turnover and quality control.…”
Section: Rna Degradation and The Mitochondrial Rnasesmentioning
confidence: 99%
See 2 more Smart Citations
“…84 Impaired RNA degradation leads to the accumulation of unprocessed precursors, introns and splicing intermediates, antisense (mirror) RNAs, and transcripts from intergenic regions of the genome. 11,12,[84][85][86] The mitochondrial genome of C. albicans, which is more compact and has shorter intergenic regions compared with S. cerevisiae, was shown to be transcribed in its entirety (pervasive transcription) in mutants deficient in the function of the main RNA degradation complex (mtEXO). 11 A range of ribonucleases, in mitochondria mostly those exhibiting exoribonuclease activities, act as general degradation factors involved in RNA turnover and quality control.…”
Section: Rna Degradation and The Mitochondrial Rnasesmentioning
confidence: 99%
“…The role played by the second mitochondrial exoribonuclease, 12 belonging to the PD-(D/E)XK superfamily and encoded by the PET127 gene, is far less clear. In S. cerevisiae, it trims the 5 0 end of the COB mRNA precursor (Figure 3), 78 as well as several other mRNAs and the 15S rRNA, 92 whereas in C. albicans it is also involved in degradation of introns.…”
Section: Pet309mentioning
confidence: 99%
See 1 more Smart Citation
“…It remained to be formally proved that it has a catalytic function [ 177 , 178 , 179 ], but a recent article showed that the pet127 PD-(D/E)XK nuclease domain is responsible for its activity in vitro. In addition, pet127 deletion and catalytic site mutants harbor the same molecular phenotype, showing that the function is linked to the catalysis of RNAs [ 180 ]. The RNA-seq study showed some intron accumulation, as well as changes in the steady-state transcriptome.…”
Section: Miscellaneous Functions Of Mitochondrial Ribonucleasesmentioning
confidence: 99%
“…The RNA-seq study showed some intron accumulation, as well as changes in the steady-state transcriptome. In vitro results suggest that the enzyme is processive and is non-selective toward ss- or dsRNAs [ 180 ]. Lastly, the authors showed that pet127 was present in LECA and is present in different phylogenetic branches (as stated in Table 1 ), but lost in animals and plants.…”
Section: Miscellaneous Functions Of Mitochondrial Ribonucleasesmentioning
confidence: 99%